Effects of phytase and mycotoxin control strategies in nursery pig diets and determining finishing pig lysine requirements - Becker, Larissa Lynn (Kansas State University, 2021)
This thesis includes three chapters addressing very practical questions facing swine nutritionists including developing a phytase release curve to quantify the release of plant-based phosphorous in swine diets, determination of the lysine requirements in finishing diets, and control strategies for diets with high levels of deoxynivalenol (DON). One experiment using a total of 360 nursery pigs was used to determine the effect of increasing phytase on nursery pig growth performance and bone ash characteristics. Two experiments using a total of 4,223 pigs were used to determine the optimal dietary standardized ileal digestible (SID) lysine (Lys) in duroc-based sired finishing pigs. Additionally, one experiment using 4,318 pigs was conducted to evaluate dietary mycotoxin control strategies on nursery pig performance and blood measures. Experiment 1 determined the available phosphorus (aP) release of GraINzyme phytase in nursery pigs. Increasing phytase from 150 to 1,500 FTU/kg in phosphorus deficient diets improved nursery pig growth performance and bone ash characteristics. Using growth performance, bone ash weight, percentage bone ash, and formulated phytase concentrations, equations were developed to predict aP release up to 1,500 FTU/kg of GraINzyme phytase for 10- to 20- kg pigs. Experiments 2 and 3 were conducted to determine the optimal dietary SID Lys in finishing pigs. Experiment 2 determined that increasing SID Lys improved growth performance and final BW. Furthermore, feed cost, feed cost/kg of gain, revenue, and income over feed cost (IOFC) increased with increasing SID Lys. In experiment 3, increasing SID Lys increased growth performance, overall market weight, and HCW. Additionally, feed cost, revenue, and IOFC increased with increasing SID Lys. Experiment 4 determined that pigs fed diets contaminated with high concentrations of DON had decreased growth performance compared to pigs fed diets contaminated with low DON concentrations. Furthermore, when feed additives such as sodium metabisulfite (SMB), Technology1, or Technology1+ were included in high DON diets, SMB supplementation led to growth performance that exceeded pigs fed the low DON diets. In summary, these experiments provide data on aP release of GraINzyme phytase, SID Lys requirements in finishing pigs, and mycotoxin control strategies in swine diets.
Keywords: Phytase; Finishing pig; Lysine requirement; Phosphorus; Nursery pigs; Deoxynivalenol